Psychopathic personality traits stress immunity and social potency moderate the relationship between emotional competence and cognitive functions in depression - Schönthaler, Elena M. D.; Dalkner, Nina; Schwalsberger, Karin; Reininghaus, Eva Z.; Reininghaus, Bernd (Frontiers in Psychiatry, 2023)
Background. Psychopathic personality traits (PPT) and depression have both been shown to worsen emotional and cognitive functions. Moreover, PPT and depression share similar underlying neuronal circuits tapping into the emotional and cognitive domains. However, little is known about the influence of PPT on emotion and cognition in individuals with depression. Objectives. This study aimed to examine the correlative relationships and moderating role of PPT in the association between emotional competence and cognitive functions in individuals with depression. Methods. Data from 373 individuals diagnosed with depression (158 males, 215 females) were examined within a cohort study. Subjects filled out validated questionnaires surveying PPT and emotional competences. Furthermore, a comprehensive neuropsychological test battery was administered. Results. Correlation analyses revealed a significant positive association between emotional competence and cognitive functions. Further, negative associations between emotional competence and the PPT “Blame Externalisation” and “Careless Nonplanfulness”, as well as positive associations with psychopathic “Social Potency” and “Stress Immunity” were found. Moderation analyses indicated a significant positive influence of psychopathic “Stress Immunity” and “Social Influence” on the relationship between emotional competence and cognitive functions. Conclusion. The findings highlight the importance of integrating PPT in depression research. Considering PPT in depression treatment could also facilitate the therapeutical process by identifying individual traits as resilience-strengthening or potentially harmful factors for depressive symptomatology. This study represents a stepping stone for further research regarding the role of personality traits in psychiatric disorders and their treatment.